Convergence of Terahertz Sciences in Biomedical Systems - Park, Gun-Sik.; Kim, Yong Hyup.; Han, Haewook; Han, Joon Koo.; Ahn, Jaewook; Son, Joo-Hiuk.; Park, Woong-Yang.; Jeong, Young Uk.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
Recent technological breakthrough in the field of Terahertz radiation has triggered new applications in biology and biomedicine. Particularly, biological applications are based on the specific spectroscopic fingerprints of biological matter in this spectral region. Historically with the discovery of new electromagnetic wave spectrum, we have always discovered new medical diagnostic imaging systems. The use of terahertz wave was not realized due to the absence of useful terahertz sources. Now after successful generation of THz waves, it is reported that a great potential for THz wave exists for its resonance with bio-molecules. There are many challenging issues such as development of THz passive and active instrumentations, understanding of THz-Bio interaction for THz spectroscopy, THz-Bio nonlinear phenomena and safety guideline, and THz imaging systems. Eventually the deeper understanding of THz-Bio interaction and novel THz systems enable us to develop powerful THz biomedical imaging systems which can contribute to biomedical industry. This is a truly interdisciplinary field and convergence technology where the communication between different disciplines is the most challenging issue for the success of the great works. One of the first steps to promote the communications in this convergence technology would be teaching the basics of these different fields to the researchers in a plain language with the help of Convergence of Terahertz Science in Biomedical Systems which is considered to be 3-4th year college students or beginning level of graduate students. Therefore, this type of book can be used by many people who want to enter or understand this field. Even more it can be used for teaching in universities or research institutions.
From the Contents: Principle of THz Radiation using Electron Beams -- Principle of THz Free Electron Laser -- Principle of linear accelerator based fs-THz generation and its application -- Electron Emitter of Carbon Nano Materials for THz Applications -- THz Generation and Propagation using Femtosecond Laser -- Principle of Solid-State based THz Generation.
Keywords: Physics; Medicine; Microwaves; Biomedical engineering; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Microwaves, RF and Optical Engineering; Biomedicine general; Biomedical Engineering; Laser Technology, Photonics